Assessing turnover of microbial biomass phosphorus: Combination of an isotopic dilution method with a mass balance model - Achat, David L.; Morel, Christian; Bakker, Mark R.; Augusto, Laurent; Pellerin, Sylvain; Gallet-Budynek, Anne; Gonzalez, Maya (Soil biology & biochemistry, 2010)
Microbial biomass phosphorus (P) can play an important role in P cycling and availability to plants by acting as a source (remineralization) or sink (immobilization) of phosphate ions (iP). To assess the role of the microbial P pools, both the dynamics (i.e. the turnover) and the size of the microbial P pools were studied in forest soils. Combining an isotopic dilution method with a modelling approach, we showed the existence of two pools of microbial P with different dynamics and therefore of different importance in soil P availability and cycling. In particular, we showed that the largest pool of microbial P (80%) had a fast turnover (nine days). Microbial P increased with an increase in soil organic matter and represented up to 53% of total P in contrasting forest soils. By combining these results with the turnover times of microbial P obtained in the modelling study, we evaluated that 8.5–17.3 kg P ha −1 of microbial P could turn over in a few days. This suggests that microbial biomass P is a potentially significant source of available iP, and that micro-organisms can play a major role in P cycling in the forest studied here. However, microbial biomass can also be in competition with the trees since most of the remineralized P could be immobilized again in the microbial turnover.